Impact of Structural Heart Disease on the Acute Complication Rate in Atrial Fibrillation Ablation: Results from the German Ablation Registry. (9th December 2013) - HOFFMANN, BORIS A.; KUCK, KARL‐HEINZ; ANDRESEN, DIETRICH; SPITZER, STEFAN G.; HOFFMANN, ELLEN; SCHUMACHER, BURGHARD; ECKARDT, LARS; BRACHMANN, JOHANNES; BECKER, RÜDIGER; STEVEN, DANIEL; ROSTOCK, THOMAS; JÜNGER, CLAUS; et al.
Acute Complication Rate in AF Ablation Introduction Catheter ablation (CA) has emerged as a widespread therapeutic option in the treatment of atrial fibrillation (AF). Currently, no safety data with regard to the impact of the underlying structural heart diseases (SHD) are available. We sought to assess the risk for acute and long‐term complications during CA of AF in relation to underlying SHD. Methods and Results We included 6, 211 patients in a prospective registry undergoing CA of AF in 41 nationwide centers. All patients were divided into 4 groups according to the underlying heart disease: No SHD (69.4%), hypertensive heart disease (HHD) (12.0%), coronary artery disease (CAD) (15.1%), and cardiomyopathy (CM) (3.6%). In univariate analysis, patients with HHD had an overall complication rate of 7.28%, whereas patients without an SHD had a significantly lower rate of 6.01% (P < 0.01). Multivariate analysis revealed that HHD (adjusted odds ratio [OR]: 1.97 [95% confidence interval (CI): 1.02–3.83], P = 0.0442) and age (years; OR: 1.04 [95% CI: 1.01–1.07], P = 0.0155) were independent predictors of severe, nonfatal complications and death. Other SHD including CAD (OR: 1.48 (0.73–3.00), P = 0.2797) and CM (OR: 2.37 [0.70–7.99], P = 0.1630) failed to reach statistical significance. Male sex was protective (OR: 0.47 [95% CI: 0.27–0.81], P = 0.0062). Conclusion In general, CA of AF has a low number of severe complications. In our prospective registry HHD emerged as an independent predictor of severe, nonfatal complications during AF ablation but other SHD including CAD and CM did not. The influence of HHD on the complication rate should be considered in patient selection.